Tingkat Kepuasan Pasien Rawat Jalan Peserta Jaminan Kesehatan Nasional Terhadap Pelayanan Kefarmasian di Puskesmas Sekupang Kota Batam - Habibie Deswilyaz Ghiffari; Delladari Mayefis; Reni Novianti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Puskesmas is a health service facility that organizes public health efforts and individual health efforts at the first level. In an effort to improve pharmacy services at the puskesmas, evaluation needs to be done by assessing patient satisfaction. The purpose of this study is to assess the satisfaction of National Health Insurance patients with pharmacy services at the puskesmas. This research was conducted for National Health Insurance patients who make up for drugs at Sekupang city of Batam. This type of research is descriptive research using a questionnaire research instrument. Data were processed using a Likert scale and the results of the study showed that the highest level of patient satisfaction with Pharmaceutical Services at Sekupang Health Center in Batam City was found in the  empathy variable (hospitality). In this study in general the results obtained from outpatient satisfaction of participants in the national health guarantee were very satisfying for respondents (85.86%).